Aeromagnetometric data of the southeast portion of the atuba complex – curitiba terrane, southernmost ribeira belt - Baldin, Michelangelo Tissi; Salamuni, Eduardo; Gimenez, Viviane Barbosa [UNESP]; Lagoeiro, Leonardo Evangelista (Universidade Federal do Rio de Janeiro, 2021)
The Atuba Complex, part of the Curitiba Terrane and the southern portion of the Ribeira Belt, occurs in the eastern region of the State of Paraná. The aerogeophysical data used in this work were made available by the Geological Survey of Brazil (CPRM), through the Paraná-Santa Catarina Project. The main objective of the research is to contribute to the study of the structural andmagnetic framework of the Atuba Complex, seeking to identify the structures and their subsurface arrangements. The fractures observed in the studied quarries and road cuts have the main NE-SW and NW-SE directions. In the Atuba Complex there are reverse, normal and sinistral or dextral strike-slip faults. The aeromagnetometric data, supported by the geology of the area and the qualitative and semi-quantitative analyzes, made it possible to interpret the structures and lineaments corresponding to the Lancinha and Curitiba shear zones, in addition to the Passaúna, Alto Iguaçu and Serra do Mar faults. The aerogeophysical images revealed that the NE-SW direction features, related to fractures of the Atuba Complex, are sectioned by the diabase dikes of the Ponta Grossa Arch in most of the studied portion, with rare exceptions in the southeast and southwest regions of the aerogeophysical maps. The ISA-GHT filter applied to the work area outlined the Curitiba Shear Zone, separating the Atuba Complex (Paleoproterozoic) from the Capiru Formation (Neoproterozoic), corroborating the geological map and lineament map of the area. Euler’s solutions showed depths lower and higher than 784 m for the NE-SW and NW-SE structures, and it is not possible to observe the depth of the main shear zones and faults, as they are obliterated by the NW-SE features.
Dados aeromagnetométricos da porção sudoeste do complexo atuba – terreno curitiba, cinturão ribeira meridional
Keywords: Aerogeophysical data; Qualitative and semiquantitative analysis; Structural framework